Perkembangan Pembiayaan Terhadap Laba Bersih Pada Bank Syariah Indonesia Sebelum dan Sesudah Merger - Agnia Afifah Adha; Nana Diana (Peneliti.net, 2023)
This study aims to fulfill and analyze whether there is a significant difference in financing between 2020 before the merger and 2021 after the merger. This study uses financing in the form of murabahah financing, mudharabah financing, and musyarakah financing, as well as net income. The research method used is quantitative research with a comparative/comparative approach. All data obtained from financial reports obtained from bank authority sites that are used as examples, namely Bank Syariah Indonesia, are taken in the form of monthly financial reports issued by Bank Syariah Indonesia. The analytical method of this study was the paired sample t-test and the Wilcoxon signed rank test, which had previously been tested for normality. The analysis results obtained prove that there are differences in murabahah financing, mudharabah financing, musyarakah financing and net profit before and after the merger.